2006
DOI: 10.1053/j.gastro.2006.07.015
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship of Abdominal Bloating to Distention in Irritable Bowel Syndrome and Effect of Bowel Habit

Abstract: Abdominal distention is a clearly definable phenomenon in IBS that can reach 12 cm. However, it only occurs in half of patients reporting bloating, and the 2 only correlate in IBS-constipation. Bloating and distention may differ pathophysiologically and this appears to be reflected in the bowel habit subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 47 publications
10
113
1
8
Order By: Relevance
“…In a study conducted by Chang et al (15) on IBS patients, all cases who experienced bloating had normal levels of psychological symptoms, including anxiety, depression, and somatization, based on the Symptom Checklist-90-Revised. In another study conducted on IBS patients by Houghton et al (43), no significant relationship was found between bloating and psychological distress. Heitkemper et al (44) were also unable to demonstrate an association between bloating and psychological distress.…”
Section: Associations With Anxiety Depression and Psychological Dismentioning
confidence: 85%
See 1 more Smart Citation
“…In a study conducted by Chang et al (15) on IBS patients, all cases who experienced bloating had normal levels of psychological symptoms, including anxiety, depression, and somatization, based on the Symptom Checklist-90-Revised. In another study conducted on IBS patients by Houghton et al (43), no significant relationship was found between bloating and psychological distress. Heitkemper et al (44) were also unable to demonstrate an association between bloating and psychological distress.…”
Section: Associations With Anxiety Depression and Psychological Dismentioning
confidence: 85%
“…The higher prevalence of bloating in IBS-C subjects may be due to the possible pathophysiology of bloating, which has been explained in previous studies: increased intestinal gas accumulation, which is mostly seen in constipated subjects due to slower than normal colonic transit, is an important cause of bloating (4,14,49). However, in some other studies, the prevalence of bloating was higher in IBS-D patients than in IBS-C subjects (4,15,30,43). Some studies have also found equally high prevalences of bloating for both IBS-D and IBS-C (5).…”
Section: Bloating In Other Gastrointestinal Disordersmentioning
confidence: 91%
“…Isso pode aparecer abruptamente e ser devido à uma contração reflexa do diafragma combinada com o relaxamento dos músculos abdominais (9) . Apesar de flatulência e distensão poderem ocorrer no mesmo paciente, inchaço geralmente reflete um fenômeno perceptivo ou sensorial, considerando-se que distensão indica uma mudança observável no diâmetro da parede abdominal (10) . Recentemente, medições objetivas confirmaram que perímetro abdominal normalmente aumenta ligeiramente durante o dia, caindo abruptamente quando deita-se para dormir e, aumentando ao levantar-se.…”
Section: Distensão Abdominal E Inchaçounclassified
“…Recentemente, medições objetivas confirmaram que perímetro abdominal normalmente aumenta ligeiramente durante o dia, caindo abruptamente quando deita-se para dormir e, aumentando ao levantar-se. O aumento diurno é maior que o normal em pacientes com SII e constipação (10) . Apenas a metade dos pacientes de SII que relatam a sensação de inchaço tem distensão acima da faixa normal.…”
Section: Distensão Abdominal E Inchaçounclassified
“…Typically, the symptom is variably reported over the months and fluctuates in intensity over daytime, particularly in the postprandial period, being worse at the end of the day and improving at night-time [11,21] . Changes in abdominal girth are greater in patients with IBS, and these patients are more likely to be symptomatic [22] . The severity of bloating may, therefore, vary from very mild to severe and uncomfortable [15] .…”
Section: Introductionmentioning
confidence: 99%